(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
For the first time in the states of the Baltic region the symbiotically fixed nitrogen has been quantified under field conditions according to total – N difference method using various legume – grass swards. Long – term field trials (1997 to 2002) were established on Stagnic Luvisol. Binary legume – grass swards were composed of Medicago varia, Galega orientalis, Trifolium repens, Alopecurus pratensis, Dactylis glomerata, Festuca pratensis, Festuca rubra, Lolium perenne, Poa pratensis and Phleum pratense. Legume and legume–grass swards were developed on similar P and K fertilizer backgrounds. Swards were cut three times during the growing season. It is concluded that fodder galega in soils developed symbiotic system with effective nodule bacteria and provided the productivity of swards 8.9 to 10.5 t ha –1 DM.Additional input of 90 kg N ha–1 resulted in changes in legume development and decreased agrophytocenosis productivity. In mixed agrophytocenosis a part of symbiotically fixed nitrogen was utilised by grasses. It was indicated by the increase of nitrogen content in the roots and above – ground parts of grasses in treatments receiving no fertilizer N. Fourfold cutting of swards also negatively influenced the activity of symbiotic system and in corresponding variants the yield and the amount of nitrogen in the aboverground parts of plants was minor in comparison with threefold cutting.